Cross-cultural comparisons of motor competence in southern brazilian and portuguese schoolchildren - Flôres, Fábio Saraiva (2021)
Aim: This study aimed to compare the MC levels of Brazilian and Portuguese schoolchildren from 4 to 11 years. Methods: One hundred and forty-eight Brazilian children were evaluated using the Motor Competence Assessment (MCA) instrument and were later compared to the existent normative values of Portuguese children for a similar age range. Results: Our findings showed that MC increased with age, and boys outperformed girls, especially in the older age group. The distribution of the Brazilian children showed that while Brazilian boys perform above Portuguese normative values in 4 of the 6 tasks of the MCA, Brazilian girls perform below those values in all tasks, except for the standing long jump. Conclusion: The differences found, especially in girls, may be related to differences in the Physical Education curricula and how school recess periods are used.